SISTEM PAKAR MENDIAGNOSA PENYAKIT HEPATITIS MENGGUNAKAN METODE VARIABLE CENTERED INTELLIGENT RULE SYSTEM (VCIRS) - Lubis, Dewi Atika; Hasibuan, Nelly Astuti; Ulfa, Kurnia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
At present the use of computer device technology has grown rapidly among the people. Most people use it not Â only for commercial purposes, but also to get information on disease detection quickly and efficiently with computer-based applications that can help the general public to find out the causes and symptoms of the disease. For this reason, a system is designed to be able to imitate the expertise of an expert in answering questions and solving a problem in accordance with the knowledge of an expert who is incorporated into a computer system. The development of artificial intelligence technology that has happened has enabled the expert system to be applied to its use in detecting diseases by using programming languages. One of them is in providing information about various problems, especially hepatitis. The expert system method used is a Variable Centered Intelligent Rule System (VCIRS) used to handle uncertainty in diagnosing hepatitis. With the facilities provided to the user, it allows the user to use this system according to their individual needs. Users are given easy information about the symptoms of hepatitis, and their prevention. This Expert System is created using the Microsoft Visual Basic 2008 programming language.Keywords: Expert system, Variable Centered Intelligent Rule System (VCIRS), Hepatitis